2003
DOI: 10.1002/art.10871
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of Fcγ receptors II and III on macrophages of rheumatoid arthritis patients results in higher production of tumor necrosis factor α and matrix metalloproteinase

Abstract: Objective. To evaluate Fc␥ receptor (Fc␥R) expression on synovial macrophages from rheumatoid arthritis (RA) patients and to determine whether this expression correlates with the production of the proinflammatory cytokines tumor necrosis factor ␣ (TNF␣), interleukin-1␤ (IL-1␤), IL-12, and matrix metalloproteinase 1 (MMP-1). We also sought to determine whether mature macrophages from RA patients express aberrant levels of Fc␥RI, Fc␥RII, and Fc␥RIII, and to determine the production of inflammatory mediators afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
3

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 59 publications
7
62
3
Order By: Relevance
“…3). Monocytes with a high level of CD16/Fc␥RIIIA expression may demonstrate more-pronounced effector mechanisms, such as phagocytosis and the production of proinflammatory cytokines (3,36), such as TNF-␣, which has been implicated in the pathogenesis of SMA by decreasing erythropoiesis (8). However, although TNF-␣ levels were elevated at enrollment for all groups, they did not differ between groups (data not shown).…”
Section: Cd16mentioning
confidence: 88%
See 1 more Smart Citation
“…3). Monocytes with a high level of CD16/Fc␥RIIIA expression may demonstrate more-pronounced effector mechanisms, such as phagocytosis and the production of proinflammatory cytokines (3,36), such as TNF-␣, which has been implicated in the pathogenesis of SMA by decreasing erythropoiesis (8). However, although TNF-␣ levels were elevated at enrollment for all groups, they did not differ between groups (data not shown).…”
Section: Cd16mentioning
confidence: 88%
“…Increased expression of Fc␥RIIIA could result from the engagement of toll-like receptors by parasite ligands, such as glycosylphosphatidyl inositol and/or parasite DNA/hemozoin complexes (34,42). A number of studies have shown that patients with rheumatoid arthritis, an IC-mediated disease (12,41), overexpress Fc␥RIIIA on peripheral as well as synovial macrophages (3,17). Individuals with the Fc␥RIIIA 158V allele have increased transcription and expression of this receptor on NK cells, but the same has not been reported for macrophages (15).…”
Section: Cd16mentioning
confidence: 99%
“…Patients with RA have an increase in the frequency of CD14 þ CD16 þ monocytes in the synovium and peripheral blood; 44 this was associated with increased TNF-a production following exposure to aggregated IgG. 44,45 DC are known to play an important role in the initiation of the immune response. Abnormalities in DC phenotype and function have been reported in RA.…”
Section: Fccriiia Allelic Polymorphisms In Ramentioning
confidence: 99%
“…Immune complexes in joints might thus provide a direct link to cytokine dependent inflammation in RA, via APCs. Coherently, APCs from RA patients have been shown to produce more TNF upon IC triggering than healthy control APCs, which can be explained by increased expression of Fc RII and Fc RIII on these cells [92,93]. High expression of the inhibitory Fc RIIb could play an important role in controlling inflammation by inhibition of activating Fc Rs and TLR4 induced cytokine production in macrophages and DCs [5,94].…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…[39,80] ICs in synovial fluid induce TNF release from monocytes. [92,93] TLR8 inhibition prevents "spontaneous" cytokine release by synovial tissue. [87] Interferogenic activity of antitopoisomerase ICs on plasmacytoid DCs.…”
Section: In Vitromentioning
confidence: 99%